2015
DOI: 10.1002/ana.24558
|View full text |Cite
|
Sign up to set email alerts
|

Tranexamic acid–associated seizures: Causes and treatment

Abstract: Antifibrinolytic drugs are routinely used worldwide to reduce the bleeding that results from a wide range of hemorrhagic conditions. The most commonly used antifibrinolytic drug, tranexamic acid, is associated with an increased incidence of postoperative seizures. The reported increase in the frequency of seizures is alarming, as these events are associated with adverse neurological outcomes, longer hospital stays, and increased in‐hospital mortality. However, many clinicians are unaware that tranexamic acid c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
158
3
5

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 219 publications
(176 citation statements)
references
References 76 publications
4
158
3
5
Order By: Relevance
“…Furthermore, the optimal dosing of intravenous TXA remains an open question. Emerging studies have also implicated TXA in systemic coagulopathies, thromboembolism, and neuropathy, possibly also stemming from off‐target effects of TXA. These observations emphasize further optimization of TXA‐based antifibrinolytic strategies for safe and effective hemorrhage control.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the optimal dosing of intravenous TXA remains an open question. Emerging studies have also implicated TXA in systemic coagulopathies, thromboembolism, and neuropathy, possibly also stemming from off‐target effects of TXA. These observations emphasize further optimization of TXA‐based antifibrinolytic strategies for safe and effective hemorrhage control.…”
Section: Discussionmentioning
confidence: 99%
“…Recent and ongoing clinical trials indicate a beneficial role of TXA in mitigating traumatic hemorrhage before and while in the hospital . At the same time, several emerging reports emphasize potential systemic risks of TXA, especially at high or repeat dose, in the context of off‐target thrombosis, thromboembolism, and neuropathy . Such findings have prompted recent research into packaging of TXA within various delivery vehicles to explore site‐localized release however, these reports are primarily focused on topical application of TXA‐loaded particles directly at the injury site.…”
Section: Introductionmentioning
confidence: 99%
“…[123] Recent literature has revealed that TA causes seizures by inhibition of gamma-aminobutyric acid receptors and alterations in cerebral blood flow and this risk is dose dependent. [18] With the possibility of seizures at higher doses and inadequate antifibrinolysis at low doses, administration of optimal dose of TA at optimal rate becomes important.…”
Section: Discussionmentioning
confidence: 99%
“…Tranexamic acid is a competitive antagonist of gamma-aminobutyric acid (GABA), which reduces the inhibition of neurotransmission thus increases excitability in neural networks. Dose dependent seizure activity has been reported with an incidence of 0.9-2.5% in non-obstetric patients, but this effect has generally not been observed with to the same degree in pregnant patients for unclear reasons (19).…”
Section: Editorialmentioning
confidence: 98%